Asset Forfeiture As An Instrument In Fighting Corruption - Lindasari , Lindasari (Corruptio, 2024)
This research employed a normative method to analyze the effectiveness of asset forfeiture in corruption cases, examining relevant laws, legal doctrines, and court decisions. The research addresses two main issues: the effectiveness of asset forfeiture in recovering state losses due to corruption and the factors influencing its success, as well as the challenges encountered in its application as a tool to combat corruption in Indonesia. The findings indicate that while asset forfeiture has the potential to recover state losses, its implementation is hindered by technical and institutional limitations, including the difficulty of establishing a direct link between seized assets and corrupt activities. Key factors influencing the success of asset forfeiture include weak coordination among law enforcement agencies, insufficiently trained personnel, and a lack of transparency in the asset seizure and management process. The primary challenge remains inconsistent law enforcement and weak oversight, which are compounded by legal and political obstacles. To enhance the effectiveness of asset forfeiture, legal reforms and the strengthening of law enforcement agencies, promoting greater synergy and professionalism in the fight against corruption, are essential.